Directors’ View on Exemption from Statutory Audit - OTHMAN , Rohana; ABIDIN , Zubaidah ZAINAL; THIRUMANICKAM , Nagathretnam (Asian Journal of Empirical Research, 2013)
Fundamentally, an audit is important to inform shareholders about the well-being of the company’s finances as it helps shareholders as well as stakeholders to make informed decisions based on the company’s performance. The current trend is however to exempt small companies from the annual audit requirement. Many studies in the United Kingdom, Australia and Singapore have addressed the issue of audit exemption for small companies. Over the years, these countries and several others have exempted small companies from the annual audit requirement. In Malaysia, it is a statutory requirement for all companies registered with the Companies Commission of Malaysia to have their annual accounts audited. However this statutory requirement is currently being reviewed to allow for an audit exemption for small companies. This study therefore explores factors that may be associated with the take-up level of audit exemption among small medium enterprises (SMEs) in Malaysia namely; value of audit, financing strategy, future plans, size of firms, director’s qualification, dependent users and audit cost. Results indicate that all six factors have a significant relationship with the take-up level of audit exemption with the exception of director’s qualification. The majority of SMEs in this study chose to continue with statutory audit even if they are not legally required to do so, showing that there is a low take-up level of audit exemption among SMEs. The results from this study provide useful information for policy makers, auditors and directors of small companies.